Modified pulse growth and misfit strain release of an AlN heteroepilayer with a Mg–Si codoping pair by MOCVD. (17th February 2016) - Soomro, Abdul Majid; Wu, Chenping; Lin, Na; Zheng, Tongchang; Wang, Huachun; Chen, Hangyang; Li, Jinchai; Li, Shuping; Cai, Duanjun; Kang, Junyong
Abstract: We report the modified pulse growth method together with an alternating introduction of larger-radius impurity (Mg) for the quality improvement and misfit strain release of an AlN epitaxial layer by the metal–organic chemical vapour deposition (MOCVD) method. Various pulse growth methods were employed to control the migration of Al atoms on the substrate surface. The results showed that the pulse time and overlapping of V/III flux is closely related with the enhancement of the 2D and 3D growth mode. In order to reduce the misfit strain between AlN and sapphire, an impurity of larger atomic radius (e.g. Mg) was doped into the AlN lattice to minimize the rigidity of the AlN epilayer. It was found that the codoping of Mg–Si ultrathin layers could significantly minimize the residual strain as well as the density of threading dislocations.